FEEDBACK’S EFFECT ON BUDGETARY SLACK AND SELF-EFFICACY AS MODERATION VARIABLE - Rahmawati, Aryani Intan Endah; ,, Supriyadi (Jurnal Akuntansi dan Keuangan Indonesia, 2020)
This study aimed to examine the effect of positive and negative feedback on budgetary slack and the interaction between feedback and self-efficacy on budgetary slack under a condition of information asymmetry. Preliminary researches have tested various ways of mitigating budgetary slack practices, which did not separate the effects of positive and negative feedback. This study hypothesized that positive feedback minimizes the potential for budgetary slack under conditions of information asymmetry—and vice versa. Additionally, high self-efficacy reinforces positive feedback in reducing budgetary slack under conditions of information asymmetry—and vice versa. By employing experimental data, this study documented the results that positive feedback significantly minimizes (the potential for budgetary slacking under conditions of information asymmetry—and vice versa. However, there is no difference in the average budget slack on managers with high or low self-efficacy, who get positive feedback.